2007
DOI: 10.1111/j.1467-9779.2007.00336.x
|View full text |Cite
|
Sign up to set email alerts
|

Piecemeal Multilateral Environmental Policy Reforms under Asymmetric Oligopoly

Abstract: We develop a general two-country model with oligopolistic interdependence in which a fixed number of firms make their output and emission decisions simultaneously. We examine the effect of multilateral reforms of emission taxes on global emission levels. With sufficient asymmetry in pollution intensities between the two countries, a proportional multilateral increase in emission tax rates can increase global emission levels. However, a multilateral equal increase of emission tax rates unambiguously reduces glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 38 publications
2
38
0
Order By: Relevance
“…12. The pollution intensity coefficient, d, is given by ÀC eq =C ee ; see Lahiri and Symeonidis (2007). 13.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…12. The pollution intensity coefficient, d, is given by ÀC eq =C ee ; see Lahiri and Symeonidis (2007). 13.…”
Section: Resultsmentioning
confidence: 99%
“…I shall assume a cost function of the end-of-pipe to capture abatement efforts by firms as in Lahiri and Symeonidis (2007). In particular, each firm i's costs depend on output, q i , and emissions, e i , where the cost function is given byC i ðq i ; e i Þ ¼ĉ i q i þ ðdq i À e i Þ 2 =2…”
Section: The Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it can be proved that, within the admissible parameter range, e s > s holds, being e s thus located in the high transport cost area. 27 Moreover, it can be shown that e s belongs to a range of s values such that an equilibrium (either P R or N R) exists. In addition, noticing that the e s threshold increases in G, when considering the upper tail of admissible G values, e s tends to become very high.…”
Section: Location Choice and Emissions Intensity Heterogeneitymentioning
confidence: 99%
“…However the extent of the technology gap per se does not lead necessarily to correct policy prescriptions. Lahiri and Symeonidis (2007) suggest that, with a small technology gap, unilateral mitigation measures lead to a contraction in global pollution. We show here that, when removing their assumptions on (a) exogenous plant location with …rms producing only in the domestic market and exporting abroad and (b) symmetry in the size of the two areas, this …nding may not hold.…”
Section: Unilateral Climate Policy and Global Emissionsmentioning
confidence: 99%